2015
DOI: 10.1120/jacmp.v16i4.5188
|View full text |Cite
|
Sign up to set email alerts
|

Single‐isocenter hybrid IMRT plans versus two‐isocenter conventional plans and impact of intrafraction motion for the treatment of breast cancer with supraclavicular lymph nodes involvement

Abstract: The purpose of this study was to compare the single‐isocenter, four‐field hybrid IMRT with the two‐isocenter techniques to treat the whole breast and supraclavicular fields and to investigate the intrafraction motions in both techniques in the superior direction. Fifteen breast cancer patients who underwent lumpectomy and adjuvant radiation to the whole breast and supraclavicular (SCV) fossa at our institution were selected for this study. Two planning techniques were compared for the treatment of the breast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The hybrid technique has been shown to provide high-quality plans that are robust to patient breathing motion. [13][14][15][16] The primary characteristic of the technique is conformal fields that deliver the majority of breast dose accompanied with a small weighting of modulated multileaf collimator (MLC) fields to fine tune the distribution.…”
Section: B | Clinical Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…The hybrid technique has been shown to provide high-quality plans that are robust to patient breathing motion. [13][14][15][16] The primary characteristic of the technique is conformal fields that deliver the majority of breast dose accompanied with a small weighting of modulated multileaf collimator (MLC) fields to fine tune the distribution.…”
Section: B | Clinical Planningmentioning
confidence: 99%
“…• x iso , y iso are the x and y co-ordinates of the plan isocenter • AE is dependent on laterality of patient hybrid IMRT technique. [14][15][16]20,21 At this point the plan is passed to the iterative optimization code. Following the iterative optimizer all plan DVH statistics were exported for analysis within the AP code.…”
Section: D | Automated Beam Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the dual-isocenter technique is traditionally applied for the treatment of patients with breast cancer with supraclavicular and axillary lymph node involvement as well as mastectomy. [12][13][14] Boman et al investigated the feasibility of utilizing dual isocenters in VMAT planning for bilateral lymph node-positive breast cancer. 12 They reported that the dose parameters slightly favored the dual-isocenter option over the singleisocenter one.…”
Section: Introductionmentioning
confidence: 99%
“…Intensity modulated radiation therapy (IMRT) has demonstrated improved ipsilateral lung sparing at moderate and high doses and a better conformal index (CI) for breast cancer and nodal irradiation compared with 3DCRT. 1,2 Although there are many published dosimetric studies investigating modulated beams for breast cancer treatment, [3][4][5][6][7][8][9][10][11] few discuss how to account for skin flashing when using inverse optimized modulated beams and the effectiveness of these techniques. The breast is a highly mobile structure for which setup reproducibility is poor, which can lead to suboptimal dose distributions and variations from the expected dosimetry if the geometry error is not properly accounted for.…”
Section: Introductionmentioning
confidence: 99%